Systematic Review of Research Trends on Critical Thinking Skills in Physics Learning - Arni, Kurnia Julianti (International Journal of Science Education and Science, 2025)
This study aims to analyze the research trends of critical thinking skills in physics learning indexed by Google Scholar during the period 2015-2024. Critical thinking skills are an important competency in physics and science education in the 21st century because of its ability to improve conceptual understanding and solve complex problems. Using descriptive methods and bibliometric analysis through VOSviewer software, this study identified patterns and trends in 1,000 indexed documents. The results showed that there was a significant increase in the number of publications related to critical thinking skills, especially in the application of problem-based learning (PBL) and the use of technology in learning. In 2023, the number of publications peaked before declining in 2024. This study also identified six dominant types of publications, with scientific articles being the most widely published. The main keywords that emerged in this trend include "PBL" "critical thinking skills", and "model". These findings are expected to provide insight into the development of research and innovation needed to improve students' critical thinking skills in the future.